Understanding the training needs of faculty members in producing research outputs: Input to faculty development program - Imee Esguerra; Billy Joe Villena; Ashlee Viagedor (CTU Journal of Innovation and Sustainable Development)
To enhance the institution’s performance in research and extension paper presentations and publications, it was essential to address the various challenges hindering faculty and researchers from meeting the institution’s annual research targets. Hence, a study was conducted via an online survey administered to 198 (64% retrieval rate) faculty members of a lone agricultural state college in Bulacan, Philippines to determine their training needs in these areas. The results indicated that more than half (52%) had already undergone relevant training on research, yet could not present or publish their papers because of limited time and funding. Only age and length of service significantly correlated with the faculty's training needs. To address these needs, the faculty development program should prioritize training in research conference identification, journal selection, presentation slide preparation, peer review process understanding, and transforming community extension reports into publishable formats. More technical and financial support is recommended to be provided to capacitate the respondents and improve their performance in paper presentation and publication.